Full configuration interaction algorithm on a massively parallel architecture: Direct-list implementation - Rossi, Elda; Bendazzoli, Gian Luigi; Evangelisti, Stefano (Journal of computational chemistry, 1998)
A parallel full configuration interaction (FCI) code, implemented on a distributed memory MPP computer, has been modified in order to use a direct algorithm to compute the lists of mono‐ and biexcitations each time they are needed. We were able to perform FCI calculations on the ground state of the acetylene molecule with two different basis sets, corresponding to more than 2.5 and 5 billion Slater determinants, respectively. The calculations were performed on a Cray‐T3D and a Cray‐T3E, both machines having 128 processors. Performance and comparison between the two computers are reported and discussed. © 1998 John Wiley & Sons, Inc. J Comput Chem 19: 658–672, 1998